To Be Oats or Not to Be? An Update on the Ongoing Debate on Oats for Patients With Celiac Disease - Spector Cohen, Inna; Day, Andrew S.; Shaoul, Ron (Frontiers in Pediatrics, 2019)
To date, the only known effective treatment for celiac disease (CD) is a strict gluten-free diet (GFD) for life. Patients with CD often find it difficult to adhere to strict GFD. Oats, compared with wheat, barley and rye, contain low levels of prolamins. Inclusion of oats in a GFD might be valuable due to their nutritional and health benefits and improvement of food variety. Therefore, they may potentially improve feeding diversity for these children and improve taste and satiety. We reviewed the literature to evaluate the safety of oats in CD patients. We have searched PUBMED, societal guidlines and national health authorities' recommendations. The following aspects were reviewed: gastrointestinal symptoms, malabsorption, serology including specific avenin antibodies, mucosal changes, avenin toxicity, immunogenicity of oats and quality of life. We also referred to wheat contamination of oat products, the safe amount of oats for CD patients and the type of oats recommended. Data support that pure oats are well tolerated by most CD patients, at moderate amounts (20–25 g/day dry rolled oats for children; 50–70 g/day for adults). Nevertheless, since the potential for sensitivity/toxicity exists, oats should be added with caution to a GFD, only after all CD symptoms including weight loss and growth disturbances have resolved, after at least 6 months of conventional GFD and probably also after normalization of serology. The need for pre exposure biopsy is unclear and should be considered on an individual basis.